Markov chain in modeling Universiti Utara Malaysia undergraduate student - Ibrahim, Adyda; Hamid, Hashibah (Universiti Utara Malaysia, 2006)
In this study, we have used Markov chain to model the flow of full time undergraduate students in Universiti Utara Malaysia (UUM) of 2003 and 2004.Through this model, we have estimated the probability of a student to complete a course and the mean times it take to complete it distinguished by age, gender, programme undertaken and the minimum entrance qualification used in enrolling at UUM.